2011
DOI: 10.1519/jsc.0b013e3181dba162
|View full text |Cite
|
Sign up to set email alerts
|

Strength Training's Chronic Effects on Muscle Architecture Parameters of Different Arm Sites

Abstract: Strength training generates alterations in muscle geometry, which can be monitored by imaging techniques as, for example, the ultrasound (US) technique. There is no consensus about the homogeneity of hypertrophy in different muscle sites. Therefore, the purpose of this study was to compare the muscle thickness (MT) and pennation angle (PA) in 3 different sites (50, 60, and 70% of arm length) of the biceps brachii and triceps brachii after 12 weeks of strength training. Forty-nine healthy untrained men were div… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
45
2
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(55 citation statements)
references
References 26 publications
5
45
2
3
Order By: Relevance
“…While strength training induced significant increases in strength, the muscle architecture of the long head of the triceps did not change significantly, which is in accordance with a previous study [21]. Interestingly, in this previous study, there was a uniform architectural adaptation at 50% and 60% of the triceps brachii length, as found here.…”
Section: Discussionsupporting
confidence: 93%
“…While strength training induced significant increases in strength, the muscle architecture of the long head of the triceps did not change significantly, which is in accordance with a previous study [21]. Interestingly, in this previous study, there was a uniform architectural adaptation at 50% and 60% of the triceps brachii length, as found here.…”
Section: Discussionsupporting
confidence: 93%
“…Studies have found changes in the pennation angle of each muscle of the quadriceps femoris 68) , as well as VL, RF 83,84) , BF 55) , MG 85) , LG 59,86) , TB 70,73,87,88) , biceps brachii 89) , brachialis 89) and supraspinous 90) . A positive correlation was shown between the absolute values of muscle thickness and pennation angle for TB 73) and each muscle of the quadriceps femoris 68) before and after the interventions.…”
Section: Evidence For Pennation Angle Changementioning
confidence: 99%
“…The correlations between muscle thickness, cross sectional area, and hold time of the prone bridge position were determined using Pearson's correlation coefficient. According to a citation for this prior study, 0.00<r< 0.19 represent very weak correlation, 0.20<r<0.39 weak, 0.40<r<0.59 moderate, 0.60<r<0.79 strong and 0.80<r< 1.00 very strong [18]. Values were considered statistically significant at p<0.05.…”
Section: Discussionmentioning
confidence: 99%
“…Triceps brachii thickness was estimated from ultrasound images, with the probe transversally positioned. The muscle thickness was defined as the distance from the interface between the muscle and bone tissue, to the interface between the muscle and fat tissue [18]. Resting triceps brachii thickness was measured with the subject prone on a bed; contraction thickness was measured as the prone subject lowered the arm to the floor and then extended the shoulder to a horizontal position with a 3-kg sandbag on the wrist.…”
Section: Measurement Of Thickness Of the Triceps Brachiimentioning
confidence: 99%